The Effect of Strategic Orientation on the Competitive Advantage and Business Performance: A Case of Batik SMEs - Iriyanto, Setia; Nurhayati, N; Suharnomo, S; Raharjo, Susilo Toto (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: In Indonesia, there is one specific type of SME (Small and Medium-Sized Enterprise) that is part of the nation’s cultural heritage, namely Batik SME (Batik is a traditional fabric). This study aims to determine the effects of Strategic Orientation on the bussiness performance and competitive advantage of SMEs of Batik in Central Java, Indonesia. Methodology: The method of this study was explanatory survey method with a type of decompressionverification study from primary data obtained from SMEs Batik with aand using PLS SEM in analyzing the data of the book. Results: The results of this study indicate that Strategic Orientation with Path coefficient (β) = 0.32 P value <0.001 (<α = 0.05), have a positive effect on Competitive Advantage with coefficient (β) = 0.46, P value <0.001 (<α = 0.05) which implies on the performance of SMEs of Batik.